Interdisciplinary Thematic Instruction in Physical Education and Health Curriculum: Practical Requirements and Design Strategies - Xianghan Xiao; He Linghui; Liu Zheng (Quality in Sport)
Research Background:‌ This study addresses the practical demands of interdisciplinary thematic teaching in physical and health education against the backdrop of deepening reforms in basic education curriculum.